Enhancing the people factor human resource issues and challenges - Lather, Anu Singh; Khatri, Puja (Narosa Publishing House, 2012)
"Enhancing The People Factor: Human Resource Issues and Challenges covers the selected papers presented by various authors comprising of corporate leaders, management practitioners, thinkers, academicians and researchers. It covers a diverse range of topics pertaining to learning organizations, leadership styles, job satisfaction, organizational commitment, employability and human resourced planning. Contemporary areas like Human Resource productivity accounting, Human Resource productivity accounting, Human resource information systems, exit interviews and Internal corporate social responsibility have been presented with a flavour of latest research and empirical treatment of the data. The book shall serve as a rich resource to a wider section of the society and the industry at large on the issues, challenges, innovations and strategies adopted by various corporate to become sustainable organizations"--Back cover.